Tissue Culture Studies on Fortunella polyandra ‘Nagami’ and ‘Meiwa’ - N., Mohamed; R.M., Taha; Hashimah, Elias; S., Abdullah; N.A., Hasbullah (ISHS, 2013)
Studies of Fortunella polyandra ‘Nagami’ and ‘Meiwa’ were carried out to observe their responses in tissue culture systems. Explant sources investigated included roots, stems, leaves and cotyledons which were cultured on Murashige and Skoog (MS) medium supplemented with different combinations and concentrations of various hormones. The hormones used were naphthalene acetic acid (NAA) and benzylaminopurine (BAP) at pH 5.8 with a temperature of 23-26°C and a photoperiod of 16 hours light and 8 hours dark. The pH of the media was also altered to include 4.8, 5.8, 6.8 and 7.8. The various explants were subjected to light and dark treatments in order to study the morphogenesis of this species. From the results, it was observed that stem and leaf explants were more responsive than other explants. The best media for regeneration and callus formation was MS supplemented with 0.5 mg/L NAA and 0.5 mg/L BAP at pH 5.8 for ‘Nagami’ and pH 7.8 for ‘Meiwa’. Regeneration was achieved via direct organogenesis and also via callus formation. The highest percentage of shoot formation (40%) was obtained from stem explants (‘Meiwa’) cultured on MS supplemented with 0.5 mg/L NAA and 0.5 mg/L BAP at pH 7.8.